Mortality burden of diabetes attributable to high temperature and heatwave under climate change scenarios in China - Sujuan Chen; Maigeng Zhou; De Li Liu; Shilu Tong; Zhiwei Xu; Mengmeng Li; Michael Tong; Qiyong Liu; Jun Yang (npj Climate and Atmospheric Science)
Abstract Climate change and diabetes pose the dual challenges to human health, yet there is a lack of evidence regarding future health burden of diabetes attributable to climate change. In this study, we used three-stage analytic strategy to project the heat-related and heatwave-related diabetes deaths by demographic characteristics and regions, during 2010–2100 in 32 major Chinese cities. Under SSP5-8.5 (high carbon emission scenario), heat-related attributable fraction of diabetes mortality is projected to rise from 2.3% (95% empirical confidence interval [eCI]: 1.1%, 3.6%) in the 2010s to 19.2% (95% eCI: 10.2%, 32.5%) in the 2090s, and estimated heatwave-related attributable fractions will increase from 0.8% (95% eCI: 0.6%, 1.0%) in the 2010s to 9.3% (95% eCI: 6.7%, 11.8%) in the 2090s. We projected that the number of heat- and heatwave-related diabetes deaths would increase from 1525 (95% eCI: 759, 2431) and 529 (95% eCI: 382, 668) in the 2010s, to 12,956 (95% eCI: 6861, 21,937) and 6312 (95% eCI: 4557, 7972) in the 2090s, respectively. Under SSP1-2.6, SSP2-4.5, and SSP3-7.0 (lower carbon emissions), we projected much lower future heat- and heatwave-related diabetes mortality burdens. Our findings might provide new insights for the development of protecting patients with diabetes from increasing temperature.